THE USE OF SUB-BITUMINOUS COAL IN COMBINATION FIRING FOR TILE, BRICK AND LIMESTONE BURNING - SUMARYONO SUMARYONO (Indonesian Mining Journal, 2012)
Combination fi ring of fi rewood and bituminous coal was recommended to reduce fi rewood consumption and to increase energy effi ciency. However, bituminous coal deposit in Indonesia has been depleted, therefore the use of sub-bituminous coal for combination fi ring should be promoted. In this work the use of sub-bituminous coal for combination fi ring was investigated in tile, brick and limestone burning. The calorifi c value of the sub-bituminous coal was only 4.6% lower than the value of bituminous coal. The increase in energy effi ciencies using sub- bituminous coal were lower than that of using bituminous coal. Compared with the use of fi rewood alone the increase in energy effi ciencies using combination fi ring of fi rewood and sub-bituminous coal in tile, brick and limestone burning were 45.7, 53.6 and 28.3% respectively. While, in the use of bituminous coal, the increase were 70.8, 75.1 and 91.9% respectively. In the combination fi ring, the fi rewood substituted by coal using sub-bituminous coal were smaller than the use of bituminous coal, i.e. for tile, brick and limestone burning, using sub- bituminous coal the substituted fi rewood were 47.7, 44.6 and 45.0% respectively while using bituminous coal there were 54.5, 50.0 and 66.0% respectively. It was revealed that the superiority of bituminous coal come from its higher content of high hydrocarbon volatiles which produced higher radiative fl ame resulting more effi cient burning processes.